2021
DOI: 10.1021/acs.est.1c00848
|View full text |Cite
|
Sign up to set email alerts
|

Acidophilic Iron- and Sulfur-Oxidizing Bacteria, Acidithiobacillus ferrooxidans, Drives Alkaline pH Neutralization and Mineral Weathering in Fe Ore Tailings

Abstract: The neutralization of strongly alkaline pH conditions and acceleration of mineral weathering in alkaline Fe ore tailings have been identified as key prerequisites for eco-engineering tailings-soil formation for sustainable mine site rehabilitation. Acidithiobacillus ferrooxidans has great potential in neutralizing alkaline pH and accelerating primary mineral weathering in the tailings but little information is available. This study aimed to investigate the colonization of A. ferrooxidans in alkaline Fe ore tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…Unsuitable pH environments are harmful to the growth and metabolism of bacteria, resulting in a decline in bacterial oxidation [ 13 ]. A. ferrooxidans can substantially alter the pH conditions of the bacteria−mineral interface and its surrounding microenvironment, consequently enhancing the mineral dissolution process [ 14 ]. Under different pH and Eh conditions, microorganisms can induce the formation of secondary minerals with different morphologies, structures, and particle sizes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unsuitable pH environments are harmful to the growth and metabolism of bacteria, resulting in a decline in bacterial oxidation [ 13 ]. A. ferrooxidans can substantially alter the pH conditions of the bacteria−mineral interface and its surrounding microenvironment, consequently enhancing the mineral dissolution process [ 14 ]. Under different pH and Eh conditions, microorganisms can induce the formation of secondary minerals with different morphologies, structures, and particle sizes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the further application of this conventional remediation approach has been hindered by the deficiencies of soil resources on site and enormous costs associated with offsite soil excavation and transportation [4]. Recently, a research hotpot, namely, in situ eco-engineering tailings into soils has been demonstrated as an efficient technique to convert the tailings into a soil-like substrate (or technosol) for mine site rehabilitation [5][6][7][8]. Yet, the methods used to construct tailing-based technosols by eco-engineering inputs of abiotic and biotic, such as organic matter, functional microorganisms, and pioneer plants are commonly time-consuming and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Given the escalating global demand for metals coupled with dwindling reserves of high-grade ores, and the urgent necessity to combat global warming and environmental pollution, biomining of mine tailings emerges as an innovative approach, effectively integrating material recycling and waste management. 1 Through this sustainable and environmentally friendly biotechnological process, we can proactively address these pressing needs and move toward a greener and more responsible future. 2 In Sudbury (Ontario, Canada), there are currently 90−120 million tons of pyrrhotite tailings (Po, Fe (1−x) S, x = 0−0.125) that have accumulated and are posing a significant threat to the environment as a potential source of acid mine drainage (AMD).…”
Section: Introductionmentioning
confidence: 99%
“…Biomining is an ecologically sound technique that harnesses the power of microorganisms to extract valuable metals from minerals. Given the escalating global demand for metals coupled with dwindling reserves of high-grade ores, and the urgent necessity to combat global warming and environmental pollution, biomining of mine tailings emerges as an innovative approach, effectively integrating material recycling and waste management . Through this sustainable and environmentally friendly biotechnological process, we can proactively address these pressing needs and move toward a greener and more responsible future .…”
Section: Introductionmentioning
confidence: 99%